Amelia jane goes up the tree - Blyton, Enid; Allwright, Deborah (Egmont London, 2002)
Naughty Amelia Jane is back and she is still getting into trouble! Debbie Allwright's illustrations perfectly capture Amelia's cheeky nature. Ages 6+.